Verificação da adequabilidade do modelo normalizado de conforto térmico utilizando a taxa metabólica determinada pelas sensações térmicas reais de usuários de ambientes industriais - Antonelli, Bruna Angela (2012)
This research aimed to verify the presence of adhesion increase in the normalized standard of thermal comfort (PMV) by using metabolic rates from users’ actual thermal sensations in industrial environments. So, this research defined the metabolic rate by multiple regression analysis, and by substituting the values of PMV by actual thermal sensations through the specific software of thermal comfort according to ISO 7730, 2005, thus getting the metabolic estimated rate. With that, new PMV values were calculated by using the values of metabolic rates, resulting in PMVtab, and PMV1 PMV2. To check which of the values of metabolic rate approached the PMV model with actual thermal sensation, an analysis of simple regression was performed, obtaining two equations for the correction of the metabolic rate table. To check the equation validity of the corrected metabolic rate, the calculation of PMV in a set of 30 measurements was carried on. The obtained result for the tabulated PMV was of R2 = 0.25; for the PMV corrected 1, of R2 = 0.26; for the PMV corrected 2, of R2 = 0.11. It demonstrates that there was no correlation between the thermal sensations which had been reported by the workers and the tabulated and corrected values of PMV. The percentage difference between Mtabulated and Mcorrected 1 and Mcorrected 2 was of 1.66% and -0.40% respectively. It is considered that for this study, in a set of 30 measurements, taking into account the workers’ actual thermal sensation, the values of the tabulated metabolic rate are not well accurate when compared to the values of PMV and to the actual thermal sensation. However, it may be considered that if the aim is to promote a small correction in the tabulated metabolic rate, one should apply on it an increasing percentage of 1.66 %.